TDCS Calculation for the Ionization of Nitrogen Molecule by Electron Impact - Alpana Pandey; Ghanshyam Purohit (Atoms, 2022)
Triple differential cross section (TDCS) results are reported for the electron impact ionization of nitrogen molecules. The TDCSs have been calculated in distorted wave Born formalism using orientation averaged molecular orbital (OAMO) approximation. The TDCS results are presented as average and weighted sum for the outer molecular orbital <semantics>3σg</semantics>, <semantics>1πu</semantics>, <semantics>2σu</semantics> and the inner <semantics>2σg</semantics> molecular orbital. The obtained theoretical TDCSs are compared with the available measurements. The results are analysed in terms of the positions and relative intensities of binary and recoil peaks. Within a first order model and for a complex molecule, a reasonable agreement is obtained with the experimental data in the binary peak region with certain discrepancies in position and magnitude in the recoil peak region.